Expression of four mitochondrial tRNAs from only two loci - Jessica M. Warren; Kasavajhala V. S. K. Prasad; Anistynn M. Mendez; Stephanie Temnyk; John P. McCutcheon (Proceedings of the National Academy of Sciences, 2026)
Transfer RNAs (tRNAs) are among the few genes retained in animal mitochondrial genomes after more than a billion years of gene loss. These ancient bacterial vestiges are often structurally aberrant and less stable than their bacterial or cytosolic tRNA counterparts. In some lineages, mitochondrial tRNAs (mt-tRNAs) have become so truncated that the loss of one or both arms has expanded our understanding of what constitutes a functional tRNA. Here, we report another radical departure from canonical tRNA gene architecture: two overlapping tRNAs produced from opposite strands of the same locus. These “mirror” tRNA pairs eliminate the need to retain separate loci for all tRNA genes, as a single locus can produce tRNAs to decode two different amino acids. We show that these mirror tRNAs are aminoacylated and demonstrate their presence in mitoribosomes. Furthermore, mirror tRNAs display strand-specific patterns of nucleotide modification and RNA editing, reflecting specific posttranscriptional maturation that depends on transcriptional orientation. This demonstration of functional, bidirectional tRNA expression reveals an unexpected strategy by which mitochondrial genomes maintain a complete set of tRNAs in the face of unrelenting gene loss. The presence of mirror tRNAs has broad implications for the evolution of tRNA-interacting enzymes, mitochondrial biology, and even the origins of the protein synthesis machinery itself.